2019
DOI: 10.1161/circheartfailure.119.006288
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Multitasking Endothelial Protein NRG-1 as a Compensatory Factor During Chronic Heart Failure

Abstract: Heart failure is a complex syndrome whose phenotypic presentation and disease progression depends on a complex network of adaptive and maladaptive responses. One of these responses is the endothelial release of NRG (neuregulin)-1-a paracrine growth factor activating ErbB2 (erythroblastic leukemia viral oncogene homolog B2), ErbB3, and ErbB4 receptor tyrosine kinases on various targets cells. NRG-1 features a multitasking profile tuning regenerative, inflammatory, fibrotic, and metabolic processes. Here, we rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 86 publications
(154 reference statements)
0
32
0
6
Order By: Relevance
“…Experiments show that expression of FAP (fibroblast activation protein alpha) [66], THBS4 [67], CD27 [68], LEF1 [69], CTHRC1 [70], ESR1 [71], CXCL9 [72], SERPINA3 [73], TRPC4 [74], F13A1 [75], PIK3C2A [76], KCNIP2 [77] and GPR4 [78] contributed to myocardial infarction. MFAP4 [79], ALOX15 [80], COL1A1 [81], APOA1 [82], PDE5A [83], CX3CR1 [84], THY1 [85], GREM1 [86], FMOD (fibromodulin) [87], NPPA (natriuretic peptide A) [88], LTBP2 [89], LUM (lumican) [90], IL34 [91], NRG1 [92], CXCL14 [93], CXCL10 [94], ACE (angiotensin I converting enzyme) [95], CFTR (ystic fibrosis transmembrane conductance regulator) [96], S100A8 [97], S100A9 [97], HP (haptoglobin) [98] [162], Zhang et al [163] and Chen et al [164] study indicated that the expression of CCL22, CCR1, FPR1, KNG1, CRISPLD2, CD38 and GPRC5A were linked with progression of ischemic heart disease. Li et al [165] showed that STEAP3 expression can be associated with cardiac hypertrophy progression.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments show that expression of FAP (fibroblast activation protein alpha) [66], THBS4 [67], CD27 [68], LEF1 [69], CTHRC1 [70], ESR1 [71], CXCL9 [72], SERPINA3 [73], TRPC4 [74], F13A1 [75], PIK3C2A [76], KCNIP2 [77] and GPR4 [78] contributed to myocardial infarction. MFAP4 [79], ALOX15 [80], COL1A1 [81], APOA1 [82], PDE5A [83], CX3CR1 [84], THY1 [85], GREM1 [86], FMOD (fibromodulin) [87], NPPA (natriuretic peptide A) [88], LTBP2 [89], LUM (lumican) [90], IL34 [91], NRG1 [92], CXCL14 [93], CXCL10 [94], ACE (angiotensin I converting enzyme) [95], CFTR (ystic fibrosis transmembrane conductance regulator) [96], S100A8 [97], S100A9 [97], HP (haptoglobin) [98] [162], Zhang et al [163] and Chen et al [164] study indicated that the expression of CCL22, CCR1, FPR1, KNG1, CRISPLD2, CD38 and GPRC5A were linked with progression of ischemic heart disease. Li et al [165] showed that STEAP3 expression can be associated with cardiac hypertrophy progression.…”
Section: Discussionmentioning
confidence: 99%
“…In heart failure, enhanced activity of NRG-1 emerges as one of the adaptive mechanisms counteracting cardiac remodeling and disease progression (73). The endogenous source of NRG-1 in the heart has been shown largely to be the microvascular and endocardial endothelium (74,75), and ECs have been demonstrated to be a crucial source of NRG-1 for cardioprotection against ischemic insult (76).…”
Section: Neuregulin-1mentioning
confidence: 99%
“…of ERBB signaling in the heart are remarkably pleiotropic with effects on endothelial cells, fibroblasts, macrophages and neuronal cells (73). Thus, the benefits reported with NRG-1 therapy may involve multiple cell types and mechanisms of action in addition to myocyte growth and/or proliferation.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations